2004
DOI: 10.1136/tc.2003.005975
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter from tobacco versus diesel car exhaust: an educational perspective: Figure 1

Abstract: Background: Air pollution is a common alibi used by adolescents taking up smoking and by smokers uncertain about quitting. However, environmental tobacco smoke (ETS) causes fine particulate matter (PM) indoor pollution exceeding outdoor limits, while new engines and fuels have reduced particulate emissions by cars. Data comparing PM emission from ETS and a recently released diesel car are presented. Methods: A 60 m 3 garage was chosen to assess PM emission from three smouldering cigarettes (lit sequentially fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 12 publications
1
50
0
1
Order By: Relevance
“…A recent survey in Australia showed that more than half of the long-haul truck drivers are exposed to ETS (Si et al 2016). The exposure to respirable suspended particles PM 2.5 originating from cigarette smoke may even be higher than that from the exhaust of a diesel heavy-duty truck, as recent studies demonstrated (Invernizzi et al 2004;De Marco et al 2016).…”
Section: Residual Confounding By Smokingmentioning
confidence: 99%
“…A recent survey in Australia showed that more than half of the long-haul truck drivers are exposed to ETS (Si et al 2016). The exposure to respirable suspended particles PM 2.5 originating from cigarette smoke may even be higher than that from the exhaust of a diesel heavy-duty truck, as recent studies demonstrated (Invernizzi et al 2004;De Marco et al 2016).…”
Section: Residual Confounding By Smokingmentioning
confidence: 99%
“…A brief report found that cigarette smoke caused ten times more particulate matter concentrations in an indoor environment than an idling eco-diesel truck engine. 7 It is evident that smoking and tobacco use are not only a great threat to general public health, but to the health of the environment as well.…”
Section: Health Effects Of Particulate Mattermentioning
confidence: 99%
“…Similar methods are described elsewhere. 7 These smoke samples were subsequently titrated with a strong acid or strong base.…”
Section: Cigarette Samplingmentioning
confidence: 99%
“…Table 3 shows that there are certainly a lot of activities and conditions which could trigger IAP, such as air fresheners, combustion appliances, water damage, cigarettes, fire and combustion equipment [10,12,13]. However, for the purpose of this study, the sources of IAP are limited to five conditions only, because they are commonly present in the indoor environment: ambient air, combustion activity, the presence of chemical products, the presence of food and beverages, and the presence of fragrances [17,[37][38][39]. The first condition of sources of indoor air pollution is the ambient air.…”
Section: Sources Of Indoor Air Pollutionmentioning
confidence: 99%